(untitled) ("Conference on Universal Science Research 2023", 2026)
This article aims to identify the laws, stages and mechanisms of development in childhood, to understand the biological (hereditary), psychological and socio-cultural factors affecting the development of a child, to help create the necessary conditions for their healthy growth and development, taking into account the individual differences of children, to identify problems, disorders and difficulties in childhood, to analyze and prevent their causes, and to develop solutions.